2023
DOI: 10.21468/scipostphys.15.2.051
|View full text |Cite
|
Sign up to set email alerts
|

Lieb-Schultz-Mattis, Luttinger, and 't Hooft - anomaly matching in lattice systems

Abstract: We analyze lattice Hamiltonian systems whose global symmetries have ’t Hooft anomalies. As is common in the study of anomalies, they are probed by coupling the system to classical background gauge fields. For flat fields (vanishing field strength), the nonzero spatial components of the gauge fields can be thought of as twisted boundary conditions, or equivalently, as topological defects. The symmetries of the twisted Hilbert space and their representations capture the anomalies. We demonstrate this approach wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 70 publications
(251 reference statements)
1
55
0
Order By: Relevance
“…Our construction generates a new kind of non-local frustration by combining two primary ingredients: (1) a non-trivial dependence of the Casimir energy of the decoration CFT on the chain length modulo some integer, and (2) a geometrical constraint which forces all loops on a given lattice to have a certain length modulo some integer. The first ingredient was recently understood as arising from effectively twisted boundary conditions for certain chain lengths [43]. More generally, our work demonstrates the importance of the coefficients c r (which encode the Casimir energy dependence on the chain length modulo some integer) as an additional property of a CFT Hamiltonian with crucial physical consequences.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…Our construction generates a new kind of non-local frustration by combining two primary ingredients: (1) a non-trivial dependence of the Casimir energy of the decoration CFT on the chain length modulo some integer, and (2) a geometrical constraint which forces all loops on a given lattice to have a certain length modulo some integer. The first ingredient was recently understood as arising from effectively twisted boundary conditions for certain chain lengths [43]. More generally, our work demonstrates the importance of the coefficients c r (which encode the Casimir energy dependence on the chain length modulo some integer) as an additional property of a CFT Hamiltonian with crucial physical consequences.…”
Section: Discussionmentioning
confidence: 66%
“…However, if c was negative, the energy per site would be minimized by taking L → ∞, leading to a loop which is macroscopically long and which can thus host a 1+1D theory with a vanishing gap. Interestingly, this scenario can be realized by choosing CFTs which are "frustrated" for certain chain lengths [43] and which can effectively behave as if c < 0, as we now show. A key insight is that, for certain CFTs, the value of c which appears in the Casimir energy is not always equal to the actual central charge and may depend on the chain length modulo some integer.…”
Section: Model and Solutionmentioning
confidence: 69%
See 2 more Smart Citations
“…A characteristic example of such a constraint is the famous Lieb-Schultz-Mattis (LSM) theorem [3] and its generalizations . Various authors [14,16,17,19,20,29,32] have suggested that these results should be phrased as 't Hooft anomalies. In particular, [32] has presented a framework to couple the lattice system to background gauge fields and to probe for anomalies as a failure of their gauge symmetry.…”
Section: Introductionmentioning
confidence: 99%